Identifying PLM themes and clusters from a decade of research literature. (28th April 2020) - Rivest, Louis; Braesch, Christian; Nyffenegger, Felix; Danjou, Christophe; Maranzana, Nicolas; Segonds, Frédéric
Product lifecycle management (PLM) encompasses a wide array of expertise, from designing green products to knowledge representation techniques. This paper characterises PLM as a research domain through the themes and clusters of a decade of scientific literature. Authors' keywords from 1, 390 research papers published from 2005 to 2015 are analysed. The co-occurrence of these 2, 947 normalised authors' keywords, connected in pairs via 11, 289 edges, indicates how PLM research themes relate to each other to form communities - or clusters. These communities are revealed by filtering the network according to the weights of the network's edges. The PLM core cluster, the PLM global cluster and the PLM overall cluster are distinguished based on the level of filtering, thus unveiling increasing levels of detail. The four major communities composing the PLM global cluster are 'interoperability', 'ontology', 'product data management' and 'lifecycle assessment'. The PLM overall cluster also reveals the 'intelligent product' community, which relates to the Industry 4.0 phenomenon. The BIM community is revealed as well, but remains isolated from the PLM overall cluster.